Pengaruh Budaya Organisasi, Kepuasan Kerja, dan Komitmen Organisasi terhadap Organizational Citizenship Behavior pada Karyawan Rumah Amal Salman - I’Shmah Zakiyyatun Nisa; Vita Sarasi (STIKes Ibnu Sina Ajibarang, 2025)
The purpose of this study is to determine the effect of organizational culture, job satisfaction, and organizational commitment on Organizational Citizenship Behavior of the management in Rumah Amal Salman. Data were obtained through a quantitative survei of 32 administrators of Rumah Amal Salman. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to test the relationship between independent and dependent variables. The results of this study illustrate that organizational culture and organizational commitment have a significant effect on Organizational Citizenship Behavior. However, job satisfaction does not significantly affect Organizational Citizenship Behavior. The implications of the study emphasize the need for management to improve sistem evaluation, career development, and internal communication to ensure sustainable job satisfaction, while maintaining a collaborative culture and organizational commitment to encourage OCB behavior that supports performance sustainability in Islamic philanthropy.